The Anteceding Role of Past Experience, Electronic Word-of-Mouth, and Emotional Intelligence on the Determinants of Purchase Intention of Green Skincare Products - Dui, Rayan; Siapno, Ezekiel; Paredes, Miguel Paolo (Future Science / FSH-PH Publications, 2024)
The researchers analyzed the factors influencing Filipino millennials' intention to purchase green skincare products based on data from 454 respondents (n=454) residing or working in the National Capital Region. The Theory of Planned Behavior mainly guides the analysis to elucidate positive and significant correlation among Past Experience, Electronic Word-of-Mouth, and Emotional Intelligence on the determinants of intention to purchase green skincare products: Attitude, Subjective Norm, and Self-Efficacy. The results show that Past Experience and Emotional Intelligence have a moderate impact, whereas Electronic Word-of-Mouth has a lesser effect on the key determinants of purchase intention. The current study proposes increased information sharing through marketing campaign strategies such as brand partnerships, the creation of social care groups, fear appeal marketing (FAM), social listening, customer surveys, sales promotions, and verbal persuasion. Future research on the subject may consider various demographics, such as Generation X and Z, and the male market. Finally, to extend the study on green skincare products considering the relationship between antecedent variables.